Health Communication in Sonar (Song Information and Reports) Events at Sonora 93.3 FM Radio Bandung - Agustrijanto Agustrijanto; Altobeli Lobodally (LPPM Stikosa - AWS, 2022)
The role of radio has undergone significant developments and changes. One example is Radio Sonora 93.3 FM Bandung. Radio Sonora is a radio that dares to raise the theme of health on one of its radio programs. With this theme, Radio Sonora shows concern for the dynamics of public health. On Radio Sonora, health messages were inserted in the show SONAR (Song Information and Reports). Through this event, listeners will get entertainment through songs and health information packaged attractively. SONAR listeners will feel free to listen to the various entertainments and be educated through the health information they convey. SONAR collaborates with several well-known hospitals in Bandung to make the information presented more convincing and exciting. This study describes how Sonora radio communicates health messages through sonar shows. This research used health communication theory as a basis and was developed through the concept of promoting health programs using radio media. The approach used is qualitative research with a case study method. The subject in this study was Radio Sonora. This research paradigm uses constructivism and descriptive methods. The results of this study show that the SONAR program is carried out with a persuasive approach that emphasizes the character of broadcasting that can persuade broadcast material by combining entertainment with health topics currently popular in the community. The conclusion and benefit of this study are that viewers get better, directed, and direct health knowledge from experts.